“We have to amplify what we saw at EBOVAC” – Assessing participant perceptions, attitudes, and acceptability of an ancillary care policy in an Ebola vaccine trial in the Democratic Republic of the Congo: A mixed methods study - Gwen Lemey; Ynke Larivière; Solange Milolo; Trésor Zola Matuvanga; Maha Salloum; Patrick Mitashi; Pierre Van Damme; Raffaella Ravinetto; Jean-Pierre Van geertruyden; Hypolite Muhindo-Mavoko; Vivi Maketa; Sibyl Anthierens (PLoS ONE, 2025)
Introduction In a vaccine trial conducted between 2019 and 2022 in Boende, a remote, resource-constrained area of the Democratic Republic of the Congo, our research team developed an ancillary care (AC) policy to provide adequate care and follow-up for concomitant adverse events (AE), whether study-related or not. The trial aimed to assess the safety and immunogenicity of an Ebola vaccine regimen among approximately 700 healthcare providers and frontliners to strengthen outbreak preparedness in this Ebola-endemic region, where access to healthcare is severely limited by poverty, weak infrastructure, and an overstretched health system. Methods A mixed-methods approach was used to assess participants’ acceptability of the AC policy. First, participants with AE completed a questionnaire (1-–5 scale; 6 questions on AC policy support, 4 on the consequences of no support, and an open comment field). Second, a telephone survey (1-–3 scale; 3 questions evaluating the AC policy, 1 on unsupported AE and an open comment field) was conducted with participants, both with and without AE. Descriptive statistics were used for quantitative data analysis, while open comments were coded qualitatively. Third, semi-structured interviews were conducted with participants who experienced a (serious) AE and either benefited from or did not benefit from the policy. Participants were selected using purposive and convenience sampling, and thematic analysis was performed. Results Of 185 individuals with AE, 290 surveys were collected, with 93.5% expressing (very) strong appreciation for the AC policy. In the telephone survey, all 311 respondents supported the AC policy and emphasized its importance, 88.1% indicated it addressed their medical needs, and 35.7% reported experiencing an AE not covered by the policy. The 17 interviews revealed three major themes: 1) Experiences with AE management and AC support; 2) Financial impact of (non-) support; 3) Expectations of AC support. Participants who received AC reported personal, medical, and financial benefits, but noted limitations, such as the scope and duration of support, variations in local healthcare practices, and administrative hurdles. Conclusion Both quantitative and qualitative findings show high endorsement for the AC policy support, regardless of participants’ personal use. This acceptability study highlights the importance of AC in clinical trials and comprehensive participant care in research.